Kynurenic Acid in Plasma and Endometrium in Bitches with Pyometra - Dąbrowski, Roman (Springer US, 2012)
Kynurenic acid (KYNA) is produced enzymatically in humans and animals from kynurenine. Reports concerning changes of kynurenine metabolism during inflammation are available in the literature. Pyometra is a pathological condition characterized by the accumulation of pus in the uterine lumen and bacterial infection. The objective of the study was to compare the serum and endometrial KYNA concentrations in healthy bitches and those with pyometra. KYNA was determined by means of high-performance liquid chromatography with fluorometric detection. The serum content of KYNA in bitches with pyometra was significantly higher than in healthy bitches. The KYNA content in the endometrium of bitches with pyometra was higher, yet the difference was not statistically significant. Our result indicates that determination of KYNA might be a marker of pyometra in bitches.